2020
DOI: 10.1093/brain/awaa228
|View full text |Cite|
|
Sign up to set email alerts
|

New genotype-phenotype correlations in a large European cohort of patients with sarcoglycanopathy

Abstract: Sarcoglycanopathies comprise four subtypes of autosomal recessive limb-girdle muscular dystrophies (LGMDR3, LGMDR4, LGMDR5 and LGMDR6) that are caused, respectively, by mutations in the SGCA, SGCB, SGCG and SGCD genes. In 2016, several clinicians involved in the diagnosis, management and care of patients with LGMDR3–6 created a European Sarcoglycanopathy Consortium. The aim of the present study was to determine the clinical and genetic spectrum of a large cohort of patients with sarcoglycanopathy in Europe. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
2
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(98 citation statements)
references
References 35 publications
10
78
2
8
Order By: Relevance
“…Concerning the impact of the genetic background, all group A's patients have at least one truncating mutation which has already been demonstrated to relate to a more severe phenotype [15]. Consistently with these data, all patients in group A lost ambulation in early teens or even before and, investigating differences between mutation groups, we observed homogeneity in patient of group A which showed a steeper decline in the variables CPK, EF, VC, FVC and FEV1.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Concerning the impact of the genetic background, all group A's patients have at least one truncating mutation which has already been demonstrated to relate to a more severe phenotype [15]. Consistently with these data, all patients in group A lost ambulation in early teens or even before and, investigating differences between mutation groups, we observed homogeneity in patient of group A which showed a steeper decline in the variables CPK, EF, VC, FVC and FEV1.…”
Section: Discussionsupporting
confidence: 87%
“…As it has been recently demonstrated that patients with truncating mutations, and therefore lower proteins' concentrations, may show a more severe clinical progression [15] and in view of our preliminary observations, in order to highlight any possible genotype-phenotype correlation, patients were analysed both as total and as grouped in two genetic subgroups: group A, for patients carrying in homozygosis or in compound heterozygosis a speci c truncating mutation in exon 3 (c.377_384duplCAGTAGGA), which is known to cause severe disease [4;18], and group B for patients with every other kind of alteration. In our cluster of patient variants were found in exon 3, exon 4, exon 6 and exon 1, which is known for causing a mild subtype of LGMDR4 [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les mutations du SGCA sont les plus répandues en Europe [7], tandis que les mutations du SGCG sont les plus courantes dans la population nord-africaine et tzigane [8]. Les mutations du SGCB sont ubiquitaires [7,[9][10][11]…”
Section: éPidémiologie (Tableau I)unclassified
“…Les sarcoglycanopathies puis les gènes impliqués ont été identifiés dans les années 1990 [14] et depuis, plusieurs études ont essayé de préciser les caractéristiques phénotypiques et génotypiques de chacune d'entre elles [11,[15][16][17]. La présentation clinique des sarcoglycanopathies est celle d'une LGMD caractérisée par une atteinte symétrique des muscles des ceintures pelvienne et scapulaire ainsi que du tronc, avec divers degrés d'atteinte cardiorespiratoire [11,16,18,19]. Un décollement des omoplates, une pseudohypertrophie des mollets et de la langue, ainsi que des CPK très élevées (> 1 000 U/l) complètent typiquement le tableau clinique (Figure 2).…”
Section: Cliniqueunclassified